Mapping Research on Islamic Fintech Using Biblioshiny-R - Aisyah As-Salafiyah; Aam; Lina Marlina (Journal of Islamic Economics Literatures, 2022)
This bibliometric study investigated the current state of documents on Islamic financial technology published by digital object identifier equipped journals listed in Dimension. The analysis focused on the description of characterictics and trends of the keywords, authors and journals. The data analyzed were 229 publications of research publications in Dimension (https://dimension.ai). The searches used to establish the study dataset were last updated on 30 January 2021. Descriptive statistical methods were used, and a bibliometric analysis was conducted using the R Biblioshiny to find out the bibliometric map. The number of articles discussing the theme of Islamic fintech has been quite large in recent years. There are many journals that publish this theme, among which the most impactful is the SSRN Electronic Journal which has many authors who research regarding this theme with various keywords. The most popular keywords used are ‘Islamic, Fintech, Financial’. This study provides an overview of trends in the most popular keywords, journals and authors in articles on the topic of Islamic fintech, thus providing information for researchers focused on research in the field of Islamic finance. In the end, this theme has the potential to continue to be developed.